The motivation of EFL public school teachers: what can self-theories tell us? (Revista Horizontes de Linguistica Aplicada, 2013)
In this paper, I report on a qualitative research study in progress, carried out with two English teachers, working in elementary education in a public school in Minas Gerais. I sought to investigate the motivation of these teachers, in light of self-theories (MARKUS; NURIUS, 1986; HIGGINS, 1987). Data collection methods include a questionnaire, an interview, classroom notes and video-stimulated recall sessions. Results show the important role played by positive and negative self-beliefs (whether actual or future) in teachers’ motivational flux. I conclude the article by emphasizing the need for encouraging the reflection on self-beliefs and affective factors that could impact on action and the sharing of experience in teacher education and in continuing education programs in order to engender a positive motivational cycle in schools.